Psychological Approaches to Shaping Patriotic Feelings in Students (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This study analyzes psychological approaches to cultivating patriotic feelings in students from both theoretical and practical perspectives. The research population comprises undergraduates aged 18–23; the focus is on the psychological factors and methods that foster patriotism. The goal is to design a set of psychological strategies that strengthen national identity, trigger intrinsic motivation, and enhance students’ patriotic spirit.Throughout the study, observation, diagnostic tests, standardized psychological questionnaires measuring emotional intelligence and social identification, as well as interactive training sessions and applied project trials were employed. The findings show that activities stimulating emotional awareness, role-playing games grounded in national values, and socially collaborative projects increase students’ patriotism indicators to a statistically significant degree (p < 0.05). In addition, goal-oriented self-reflection exercises that bolster intrinsic motivation produced positive changes in national identification scores.The scientific novelty lies in the development of an integrative model of psychological approaches that combines emotional intelligence, social identification, and motivational factors, offering a comprehensive practical algorithm for shaping patriotic feelings in students. Practically, the training module can be implemented in higher-education “Spirituality and Enlightenment” courses and in volunteer club programs.